A correlational analysis of the use of book and internet on the level of learning of fourth year SPED-ISEC students in Iloilo City. - Golez, Prince Couen E.; Pausa, Mary grace; Umipig, Paulyn Ann A. (2006.)
This study conducted in June-October 2006, aimed to find out whether or not there is a correlation between the level of learning and the use of books and Internet of the 4th year high school students of SPED-ISEC. The level of learning was further categorized into four classifications: frequency of use, level of exposure, purpose of using a certain medium, and the integrated part of the survey., The researchers conducted a survey to determine the exposure of the students to books and the Internet and administered tests to measure their level of learning of students in using these media as information resources. The study revealed that there was a positive correlation between the frequency of use of book and Internet with the level of learning of the 4th year SPED-ISEC students. However, the value of the correlation was very low. There were other factors that influenced the results: the choices made by the respondents in the survey, their involvement toward the materials provided , and the level of learning of the students.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Correlational analysis -- Book and Internet -- Educational learning